DIGITALISASI AKUNTANSI PADA UMKM: PERSPEKTIF PELAKU USAHA - Amy Septrina Tampubolon; Ersanti Ersanti; Ahmad Kamal Jama; Rebeka Meidiana Purba; Nursyam Ar (JURNAL LENTERA BISNIS, 2026)
Digital transformation has brought significant changes to various aspects of business management, including accounting systems in Micro, Small, and Medium Enterprises (MSMEs). Accounting digitization is one solution to improve the efficiency, accuracy, and quality of business financial management. However, the level of adoption of digital accounting technology in MSMEs still varies and is influenced by various factors, both internal and external. This study aims to explore business actors' perspectives on accounting digitization, including their level of understanding, perceived benefits, implementation barriers, and its impact on business preservation and continuity. The study used a qualitative approach with descriptive methods. Data were collected through in-depth interviews, observation, and documentation of MSMEs who have and have not implemented digital accounting systems in their business activities. Informants were selected using a purposive sampling technique based on certain criteria relevant to the research objectives. Data were analyzed through the stages of data reduction, data presentation, and conclusion drawing, and their validity was tested using source and method triangulation techniques. The results showed that most MSMEs have a fairly good understanding of accounting digitization as the use of technology in recording and managing business finances. Accounting digitization offers various benefits, such as ease of transaction recording, accurate financial reports, time efficiency, and ease of real-time financial monitoring. Furthermore, the use of digital accounting systems helps businesses make more informed business decisions based on available financial information. However, the implementation of accounting digitization still faces several obstacles, including limited digital literacy, lack of technical skills, application usage costs, and resistance to the transition from manual to digital systems. Research also finds that government support, training, mentoring, and easy access to technology are important factors in driving the successful implementation of accounting digitization in MSMEs.